Exploring killer business domains for drones in Korea - Hyeseon Kwon; Seongcheol Kim (International Telecommunications Society (ITS), 2018)
Commercial drone is one of the most promising businesses in IoT industry. However, even if we classify domestic commercial drones market roughly, it still is a broad field since there are diverse domains such as delivery service, media, assessment‧business monitoring, agriculture, vehicles, sports‧healthcare, and education. In order to promote domestic commercial drone market, this study will try to discover which domain will be the killer. Therefore, this study sheds light on the emerging commercial drone market in Korea. In order to proliferate the commercial drone market in Korea, this study proposes an AHP model for assessing the killer business domain for drones which consists of 9 technology, market, and policy factors. The model was applied to assess and compare the prospect of three drone business domain; media drone, assessment‧business monitoring drone, and entertainment drone. By inviting the perception of 39 drone experts, the results showed that assessment‧business monitoring drone is the most promising drone in Korea.
Keywords: 330; commercial drone; Unmanned Aerial Vehicle(UAV); Analytic Hierarchy Process(AHP)